Modelling of aortic aneurysm and aortic dissection through 3D printing. Issue 1 (30th January 2017) - Ho, Daniel; Squelch, Andrew; Sun, Zhonghua
Abstract: Introduction: The aim of this study was to assess if the complex anatomy of aortic aneurysm and aortic dissection can be accurately reproduced from a contrast‐enhanced computed tomography (CT) scan into a three‐dimensional (3D) printed model. Methods: Contrast‐enhanced cardiac CT scans from two patients were post‐processed and produced as 3D printed thoracic aorta models of aortic aneurysm and aortic dissection. The transverse diameter was measured at five anatomical landmarks for both models, compared across three stages: the original contrast‐enhanced CT images, the stereolithography (STL) format computerised model prepared for 3D printing and the contrast‐enhanced CT of the 3D printed model. For the model with aortic dissection, measurements of the true and false lumen were taken and compared at two points on the descending aorta. Results: Three‐dimensional printed models were generated with strong and flexible plastic material with successful replication of anatomical details of aortic structures and pathologies. The mean difference in transverse vessel diameter between the contrast‐enhanced CT images before and after 3D printing was 1.0 and 1.2 mm, for the first and second models respectively (standard deviation: 1.0 mm and 0.9 mm). Additionally, for the second model, the mean luminal diameter difference between the 3D printed model and CT images was 0.5 mm. Conclusion: Encouraging results were achieved with regards to reproducing 3D models depicting aortic aneurysm and aortic dissection. Variances in vessel diameter measurement outside a standard deviation of 1 mm tolerance indicate further work is required into the assessment and accuracy of 3D model reproduction. Abstract : This study shows the feasibility of using 3D printing in cardiovascular disease, with results showing accuracy of replicating anatomic structures as well as pathologies involving the aorta.